2017
DOI: 10.2106/jbjs.16.01184
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Displaced Midshaft Clavicle Fractures: Figure-of-Eight Harness Versus Anterior Plate Osteosynthesis

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 30 publications
0
54
0
Order By: Relevance
“…For 6 out of the 8 fracture types with available data on SAEs from at least two trials, no differences were demonstrated between surgical and non-surgical treatment. For displaced midshaft clavicula fractures (14 trial (n = 1394)) [24][25][26][27][28][29][30][31][32][33][34][35][36][37], surgery was associated with a smaller risk of SAEs than non-surgical treatment (RR 0.62 (0.42 to 0.92)). For distal radius fracture (5 trials (n = 436)) [59-61, 65, 80], surgery was associated with a greater risk of SAEs than non-surgical treatment (RR 3.10, 95% CI 1.42 to 6.77).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…For 6 out of the 8 fracture types with available data on SAEs from at least two trials, no differences were demonstrated between surgical and non-surgical treatment. For displaced midshaft clavicula fractures (14 trial (n = 1394)) [24][25][26][27][28][29][30][31][32][33][34][35][36][37], surgery was associated with a smaller risk of SAEs than non-surgical treatment (RR 0.62 (0.42 to 0.92)). For distal radius fracture (5 trials (n = 436)) [59-61, 65, 80], surgery was associated with a greater risk of SAEs than non-surgical treatment (RR 3.10, 95% CI 1.42 to 6.77).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Besides 1 study [26] whose full text cannot be obtained, 3 articles including 1 QRCT, [27] 1 cohort study, [28] and 1 duplicate study (Summary and Review) [29] were excluded after reading the full texts. Finally, 9 RCTs [1416,22,3034] were included in the present meta-analysis. The details of the literature retrieval were shown in the flowchart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using random-effects model, there was no significant difference between the 2 groups (RR, 0.53[95%CI 0.23–1.25], P = .15). Sensitivity analysis found that heterogeneity was significantly lower after removing the study by Tamaoki et al, [16] and appearance dissatisfaction rate was relatively lower in the ORPF group (RR, 0.35 [95% CI 0.23–0.55], P < .001). Based on above results, we cautiously drew the conclusion that appearance dissatisfaction rate in the ORPF group was not higher than that in the non-surgical treatment group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations